Enhancing intercultural teaching competencies through internationalisation of pre-service primary foreign language teachers - Brzosko-Barratt, Katarzyna; Rozmanič, Tina; Baldassari, Silvia; Dagarin Fojkar, Mateja (Neofilolog, 2025)
As schools are getting linguistically and culturally more diverse, it is necessary to develop teachers’ intercultural teaching competencies. This paper focuses on a transnational study conducted during three editions of a blended intensive programme in which 107 pre-service primary foreign language teachers from three countries participated. The goals of the programme were to engage future teachers in practices strengthening international and intercultural dimensions, and to broaden their knowledge and skills on language and content integration in different European contexts. The results of the study, which was conducted using different methods of data collection, including focus group interviews, surveys, analysis of lesson plans and classroom observations, showed the development of intercultural foundational competencies, i.e., strengthening of participants’ self-awareness and self-reflexivity in developing their cultural and disciplinary identities. The participants also developed competencies necessary to recognise learners’ needs to build effective classroom communities. Participants found it difficult to respond to diversity in the classroom by planning and implementing global and intercultural learning activities for pupils. The study shows that internationalisation is crucial for pre-service primary language teachers to improve their professional and intercultural competencies.